Optimal usage of biomass for energy purposes toward sustainable development-a case of Macedonia - Kanevche, Aleksandra; Dedinec, Aleksandar; Kanevce, Gligor (My University, 2016)
One of the main goals for sustainable development of a country is providing sustainable energy resources, which means satisfying the current needs for energy without compromising the future generations. Moreover, sustainable energy resources primarily involve greater inclusion of renewable energy sources. The biomass is the most widely used renewable energy source, mainly because of its relatively low price and its availability. However, in order for the biomass to stay a renewable energy source, it must be used rationally and with a plan, which primarily requires a detailed analysis of the current situation and resources. Therefore, the aim of this paper is to calculate the optimal utilization of biomass in energy purposes, taking into account the sustainable development of a country. As an example, in this paper Macedonia is considered. A detailed analysis of the data sources related to biomass is made and several different indicators that describe the current situation in Macedonia are presented. Furthermore, several scenarios are defined in this paper in order to calculate the optimal share of biomass in the overall energy mix in Macedonia for the next 20 years, using the MARKAL model.
Keywords: biomass, sustainability, optimal share of biomass